Analisis Ketersediaan Air dengan Metode F. J. Mock di Das Lowo Rea Kabupaten Ende untuk Kebutuhan Air Irigasi - Nurdin, Samsul Alam ; Khaeruddin, Dian Noorvy ; Sulistyani, Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Lowo Rea Watershed (DAS) is a water source that has the potential for an irrigated area of ??1500 ha which is currently utilized only 889 ha, meaning the remaining unused land area of ??611 ha. The purpose of this study was to analyze the availability of water by the F. J. Mock method in the Lowo Rea watershed for irrigation water needs. Rainfall data from 2007 to 2016, Paupanda Pattern Station, Soria / Maukaro Station and Nanganio Pattern Station, this calculation also uses maumere climatology station data. The average rainfall in the Lowo Rea Watershed is 1037 mm / year. From the results of data analysis, it can discharge 80% on average per year 124.07 million / m3 for a discharge analysis of 95% averaging 43.20 million / m3 annually. Furthermore, the analysis of water needs in irrigated land for functional land MT1 889 ha MT2 165 ha and potential land MT1 1500 ha MT2 165 ha. Residual water from irrigated land used for household water needs 60 liters / person from the analysis of household water needs experienced a deficit of -0.02 million / m3 in the second period of August 2018 to 2037 while for other months and years surplus to the irrigated districts of Ende, Detusoko, Wewaria, Detukeli, Maukaro, and Maurole for the remaining water from domestic household water needs of 52 million / m3.